Fu-lin dances in medieval Chinese art - Byzantine or imaginary? - Liveri Angeliki (Zbornik Radova Vizantološkog Instituta, 2019)
Chinese artists, active from the Tang dynasty to Northern Song dynasty, created famous paintings including Fu-lin musical and dancing scenes; as e. g. Yan Liben, Wu Daozi and Li Gonglin. The most of these works are unfortunately lost; thus, we have information only from written descriptions to reconstruct them. Some researchers identify Fu-lin with the Byzantines; others disagree with this interpretation. Therefore, it is worthwhile to study whether the musical and dance motifs that referred to Fu-lin and were used by the above mentioned Chinese artists and literati can be identified with Byzantine elements and their performers with Byzantines ones.